Knee Osteoarthritis with Chronic Quadriceps Tendon Rupture Treated with Total Knee Arthroplasty and Extensor Mechanism Allograft Reconstruction: A Case Report. Issue 3 (July 2018) - Piatek, Allison Z.; Lee, Patrick; DeRogatis, Michael J.; Boyajian, David A.; Issack, Paul S.
Abstract : Case: A 51-year-old male construction worker with a history of chronic quadriceps tendon rupture presented with no active knee extension and tricompartmental knee osteoarthritis. He underwent simultaneous total knee arthroplasty and extensor mechanism allograft reconstruction. At 4 years postoperatively, the patient had pain-free knee function and active extension. Conclusion: The combination of a chronic quadriceps tendon rupture with lack of active knee extension and knee osteoarthritis is a rare and challenging problem. To our knowledge, this combined diagnosis and the treatment described in this case report have not been reported previously in the literature.